(untitled) (Revista Brasileira de Contabilidade e Gestão, 2012)
Since 1950 architects and urbanists aims an own counsil, but justin the end of 2010 the professionals had approved a law that creates and regulates the new council. As said our intention is to identificate the normative hierarchy besides the regulation of the architect and urbanist and engineer profession and the collision points.